Intuitive expertise and financial decision-making - Grant, Michael (Senior lecturer) (New York, NY : Routledge, 2023)
"This book provides insights into the hidden role of intuitive expertise in financial decision-making. The authors show and discuss how expertise combined with intuitive judgements positively affect decision-making outcomes. The book builds on the latest academic studies in this emergent field. In combination with the academic perspective the authors provide a field study that they conducted in the context of mergers and acquisitions (M&As), a common and critical strategic investment for companies. The interviews were carried out with experts and decision-makers in large and successful international companies (i.e. M&A experts, CEOs, CFOs and Board members). The book provides a solid theoretical and empirically based grounding of the topic. In addition, it offers suggestions to practitioners on how they can develop and nurture intuitive expertise in strategic investment decision-making. The report of the field study provides examples and quotes from interviews to visualize findings, thus helping practitioners gain understanding and insights from the text. The authors also discuss the downsides of intuitive expertise such as biases and flawed decision-making. For scholars, students and professionals, the book offers a concise and up-to-date summary of an emergent stream of research, exploring how cognition and judgement affect financial decision-making"--
Keywords: Investments -- Decision making; Finance -- Decision making; BUSINESS & ECONOMICS / Accounting / Financial; BUSINESS & ECONOMICS / International / Accounting; BUSINESS & ECONOMICS / Banks & Banking